Influence of integrated use of microbial inoculants and inorganic fertilizers on growth and nutrient dynamics of oil palm seedlings: INFLUENCE OF MICROBIAL INOCULANTS AND INORGANIC FERTILIZERS ON OIL PALM SEEDLINGS - VEERAMACHANENI SUNEETHA; K RAMACHANDRUDU (Journal of Oilseeds Research, 2017)
Nurseryexperiment was conducted to observe influence ofmicrobial fertilizers on growth and nutrient dynamics of oil palm (Elaeis guineencies Jacq.) seedlings for two years. Azotobacter chroococcum, Azospirillum brasilense, Bacillus megaterium, Frateuria aurantia and Glomus aggregatum were used individually, combinedly and integrated with chemical fertilizers. Promising results for seedling height, leaves, root volume and dry matter were recorded under microbial fertilizers+25% recommended dose of chemical fertilizers. Maximum availability of organic carbon, phosphorus, iron, manganese, copper, zinc and boron with microbial fertilizers+25% recommended dose of chemical fertilizers, potassiumin Frateuria aurantia and calciumand magnesiuminAzospirillum brasilense were observed in potting mixture. Similarly, significant enhancement in total uptake of nitrogen, phosphorus, potassium, calcium, magnesium, iron, manganese, copper and zinc by seedlings with microbial fertilizers+25% recommended dose of chemical fertilizers. Integrated use of microbial fertilizers with lower dose of chemical fertilizers played a significant role in enhancing growth, soil fertility and nutrient uptake.